2016
DOI: 10.1590/1806-9061-2015-0164
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Newcastle Disease Virus, Avian Influenza Virus and Mycoplasma Gallisepticum in Wild Birds Near Commercial Poultry Farms Surrounded by Atlantic Rainforest Remnants, Southeastern Brazil

Abstract: The geographic overlap between areas of Atlantic rainforest and human activities allows interactions to occur between humans and wild and domestic animals. Despite the great importance of the domestic animal-wildlife-human interface that occurs at poultry farms in terms of public health, economic production and wildlife conservation, there are few studies in Brazil examining the distribution and health of wild birds that interact with poultry farms. From January to December 2010, mist nets were used to capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Similarly, the higher MG prevalence in seized birds probably reflects the poor hygiene and stressful conditions to which these birds are subjected [59]. Even though MG exposure has been reported for wild birds [71,74,77], the lack of qPCR-based positive samples for MG is in agreement with another Brazilian study that sampled wild birds in poultry farms surrounded by forest remnants [78]. Even though none of the positive individuals in our sample showed any clinical evidence of infection, differential MG-susceptibility across bird species has been observed after experimental infections that resulted in both clinical and subclinical symptoms [79], which also occurred in wild birds [74,77,80].…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, the higher MG prevalence in seized birds probably reflects the poor hygiene and stressful conditions to which these birds are subjected [59]. Even though MG exposure has been reported for wild birds [71,74,77], the lack of qPCR-based positive samples for MG is in agreement with another Brazilian study that sampled wild birds in poultry farms surrounded by forest remnants [78]. Even though none of the positive individuals in our sample showed any clinical evidence of infection, differential MG-susceptibility across bird species has been observed after experimental infections that resulted in both clinical and subclinical symptoms [79], which also occurred in wild birds [74,77,80].…”
Section: Discussionsupporting
confidence: 70%
“…Many epidemiological aspects of MG infection concerning the pathogen's carriers, contagiousness, and spread in different geographic areas and among different species of birds are not widely understood. The increase in the number of MG reservoirs could disrupt the eradication of the pathogen in poultry, especially in developing countries in which the appropriate survey and eradication programs have not been introduced and biosecurity requirements are not met [47,78]. Knowing the range of potential hosts of MG and mechanisms of infection spread among species is important from the epidemiological point of view, but systematic epidemiological reviews and meta-analyses on the occurrence of MG in wild birds have not been carried out yet.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that synanthropic species of Passeriformes and Columbiformes may interact directly or indirectly with chickens in poultry farms in South America. 66,67 Although no evidence of AIV infection was detected thus far in such synanthropic birds near poultry facilities, such studies stress the need for the development and implementation of biosecurity measures that effectively prevent wild birds from closely interacting with poultry in farms. 67 Although domestic birds may pose the most significant risk in terms of AIV gene flow from wild birds to humans, the possibility of direct AIV transmission from wild birds to humans should not be dismissed.…”
Section: Implications For Human Healthmentioning
confidence: 99%
“…66,67 Although no evidence of AIV infection was detected thus far in such synanthropic birds near poultry facilities, such studies stress the need for the development and implementation of biosecurity measures that effectively prevent wild birds from closely interacting with poultry in farms. 67 Although domestic birds may pose the most significant risk in terms of AIV gene flow from wild birds to humans, the possibility of direct AIV transmission from wild birds to humans should not be dismissed. For instance, traditional communities from some regions of South America may engage in cultural practices that provide opportunities for the transmission of AIV.…”
Section: Implications For Human Healthmentioning
confidence: 99%
See 1 more Smart Citation